Comparative diagnostic efficacy of serum Krebs von den Lungen-6 and surfactant D for connective tissue disease-associated interstitial lung diseases: A meta-analysis. Issue 16 (April 2020) - Zhong, Danli; Wu, Chanyuan; Bai, Jingjing; Hu, Chaojun; Xu, Dong; Wang, Qian; Zeng, Xiaofeng
Abstract: Purpose: The aim of the study was to estimate and compare the diagnostic accuracy of serum Krebs von den Lungen-6 (KL-6) and surfactant protein D (SP-D) for identifying interstitial lung disease (ILD) from non-ILD among connective tissue disease (CTD) patients. Materials and Methods: Original articles on the diagnostic accuracy of serum KL-6 and SP-D in differentiating CTD-ILD from CTD-nonILD were identified from three public databases. The overall quality of evidence and methodologic quality of each eligible study were assessed by the Grading of Recommendations, Assessment, Development and Evaluation approach and Quality Assessment of Diagnostic Accuracy Studies, respectively. We used the bivariate model to calculate random-effect sensitivity, specificity, likelihood ratios, and area under curve. Furthermore, trial sequential analysis (TSA) was used to determine whether sample sizes incorporated in the meta-analysis were powerful for evaluating the diagnostic utility. Bayesian network analysis was performed to compare the diagnostic accuracy of 2 serum biomarkers in differentiating ILD among CTD patients and various subgroups. Results: Twenty-nine studies were included in the quantitative synthesis. No threshold effects were observed (all P values >.05). For diagnosis of ILD among CTD patients, overall sensitivity and specificity of serum KL-6 were 0.76 (95% confidence interval [CI]: 0.68–0.82) and 0.89 (95% CI: 0.83–0.93), whereas those for serum SP-D were 0.65 (95% CI: 0.45–0.80) and 0.88 (95% CI: 0.80–0.93). Comprehensive comparison of 2 circulating biomarkers using back-calculated likelihood ratio (LR) demonstrated that serum KL-6 corresponded to a higher LR+ and a lower LR– in comparison to serum SP-D, as well as in SSc-ILD. TSA indicated that evidence for serum KL-6 and SP-D in identifying CTD-ILD is powerful; nonetheless, more trials were needed for validation of serum KL-6 and SP-D in differentiating CTD-ILD subtypes, including different CTD and ethnicities. Conclusions: This meta-analysis suggested that serum KL-6 had superior diagnostic accuracy to SP-D for differentiating ILD from non-ILD among CTD patients, providing a convenient and non-invasive approach for screening and management of ILD among CTD patients. Abstract : Supplemental Digital Content is available in the text